A qualitative analysis of young people's experiences of receiving a novel, client‐led, psychological therapy in school. Issue 4 (26th August 2019) - Churchman, Anamaria; Mansell, Warren; Al‐Nufoury, Yasmin; Tai, Sara
Abstract: Mental health problems often arise in adolescence. Schools have been recognised as a potential hub for support; however, delivering targeted interventions in schools can be difficult due to impracticalities. Subsequently, students have little or no say in the support process. Given the importance of control in well‐being, the current study explored how adolescents experienced Method of Levels, a therapy that allowed them to choose if and when to attend therapy. Interviews with 14 adolescents were conducted and then analysed using thematic analysis. Three main themes were identified; therapy style, therapy experience and exploring problems. An additional overarching theme was generated, regarding choice and control. Findings indicate that adolescents value having choice and control. This made the therapy style accessible, enhanced the therapeutic experience and ultimately facilitated the process of exploring problems.